Reading Matthew with Monks : Liturgical Interpretation in Anglo-Saxon England - Olsen, Derek A. (Book collections on Project MUSE., 2015)
In Reading Matthew with Monks, Derek Olsen seeks to evaluate whether early medieval monastic biblical interpreters can serve as effective conversation partners for modern readers who are committed to broadening their reading of Scripture. Olsen puts the interpretations of four modern Scripture commentaries in conversation with AElfric of Eynsham's interpretations of four texts from the Gospel of Matthew. In so doing, he clarifies early medieval monastic interpretive contexts and assesses their usefulness in modern scholarship. As outsiders in modern critical debates, AElfric and his sources may provide alternative approaches or perspectives that open interpretive possibilities where modern interpreters are locked in disagreement. Early medieval monastic interpreters can serve as excellent guides for understanding the potential for moral, spiritual, or formative meanings of a biblical text. By adding their voices to modern hermeneutics, modern readers can find new depth in biblical texts.